(POST) COLONIAL ENCOUNTERS IN THE POSTSOCIALIST CITY: RESHAPING URBAN SPACE IN SARAJEVO. Issue 4 (December 2016) - Badescu, Gruia
ABSTRACT: This article argues that postcolonial lenses can be useful in understanding postsocialism in particular urban situations, examining the postsocialist city of Sarajevo as an arena of postcolonial practices, processes and relationships. The city discussed, Sarajevo, provides a rich example of entanglements and relationships, both historical and of more recent origin. The article discusses with a postcolonial lens processes of urban reconstruction, specific to Sarajevo as a "post‐conflict city", but focuses on later urban development patterns, which in fact echo the general trends of postsocialist urban transitions in the broader region. As such, the article aims to unpack how the flows of capital reflect a postcolonial configuration of relationships between local elites, international actors and urban space. The case of Turkish investments reflects an increasing re‐forging of ties between the metropole and the former province of the Ottoman Empire. New relationships also emerge, but with similar dynamics – the cases of Saudi investment and the construction of the US Embassy are explored to highlight the role of the local elites. The article argues that the postcolonial lens is useful to explore the relationship between the local elites and international capital in postsocialist cities, highlighting processes, practices, and relationships that are complementary to political economy‐based urban geographies.